Engineering nematode resistant plantains for sub-Saharan Africa - Tripathi, L.; Tripathi, J.N.; Roderick, H.; Atkinson, H.J. (International Society for Horticultural Science, 2013)
Banana and plantain (Musa spp.) are major staple foods and a source of income for millions in tropical and subtropical regions. Most of the bananas and plantains grown worldwide are produced by small-scale farmers for home consumption or sale in local and regional markets. Many pests and diseases significantly affect Musa cultivation. Nematodes pose severe production constraints, with losses estimated at about 20% worldwide. Locally, however, losses of 40% or more occur frequently, particularly in areas prone to tropical storms that topple the plants. Pest management in banana is mainly based on crop rotation and chemical control. However, crop rotation is not often practiced and nematicide use is usually not affordable for subsistence farmers. Limited sources of nematode resistance and tolerance are present in the Musa gene pool. Some resistance has been identified against one of the most damaging nematode species, the burrowing nematode (Radopholus similis), but this needs to be combined with consumer-acceptable traits. Furthermore, several species of nematodes are often present together, requiring a broad spectrum resistance able to control not just Radopholus but other damaging nematodes, such as species of Pratylenchus and Helicotylenchus. Biotechnology offers sustainable solutions to the problem of controlling plant parasitic nematodes. The International Institute of Tropical Agriculture (IITA), in partnership with the University of Leeds, UK, has developed transgenic plantain for nematode resistance using maize cystatin and synthetic repellent genes. The transgenic plantain lines were validated by PCR and western blot analysis for presence and expression of transgene respectively. The efficacy of the genes against nematode resistance has been proven in glasshouse trials which will be further tested in confined field trial. Genetically modified plantain with resistance to all nematodes would be a substantial breakthrough in Musa pest management for Africa and elsewhere.